2004
DOI: 10.1901/jaba.2004.37-53
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Task Difficulty and Type of Contingency on Students' Allocation of Responding to Math Worksheets

Abstract: This study investigated students' allocation of responding as a function of task difficulty and type of reinforcement contingency (i.e., accuracy based or time based). Four regular education fourth-grade students were presented with two identical stacks of easy and then difficult math worksheets using a reversal design. Regardless of condition, completing problems from each stack of worksheets was reinforced according to a different contingency; one required correct completion of math problems (accuracy based)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 18 publications
(18 reference statements)
2
23
0
Order By: Relevance
“…This increase constitutes a significant difference in allocation between the two experiments, t(8) 5 3.92, p 5 .004 (one tailed). In light of the increase in the bias parameter of the generalized matching equation and the discrimination indexes, these data provide further evidence that the effort manipulation successfully biased responding toward the less effortful alternative in accordance with previous behavioral accounts of effort manipulations (Bradshaw et al, 1981;Cuvo et al, 1998;Lannie & Martens, 2004;Neef & Lutz, 2001;Neef et al, 1994;Weeks & Gaylord-Ross, 1981).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This increase constitutes a significant difference in allocation between the two experiments, t(8) 5 3.92, p 5 .004 (one tailed). In light of the increase in the bias parameter of the generalized matching equation and the discrimination indexes, these data provide further evidence that the effort manipulation successfully biased responding toward the less effortful alternative in accordance with previous behavioral accounts of effort manipulations (Bradshaw et al, 1981;Cuvo et al, 1998;Lannie & Martens, 2004;Neef & Lutz, 2001;Neef et al, 1994;Weeks & Gaylord-Ross, 1981).…”
Section: Discussionsupporting
confidence: 86%
“…Approaching academic performance and related behaviors with an understanding of the influence of task effort on responding may prove to be beneficial for instructional design as well as for behavioral programming. For example, when students are assigned work to complete, they are placed in a choice situation that is partly under the control of task difficulty as well as the reinforcement contingencies associated with each alternative (e.g., Lannie & Martens, 2004). Previous research has shown that children choose not to complete difficult tasks when given less effortful alternatives (e.g., Berkowitz & Martens, 2001;Neef & Lutz, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contingency included a permanent response product in order to decrease the likelihood that on‐task behavior would come under the control of the therapist entering the room (i.e., Aaron starting work when a therapist entered and stopping when the therapist left). In addition, including a contingent relation such as problem completion may increase the likelihood that the participants show preference for the procedures (Lannie & Martens, ).…”
Section: Methodsmentioning
confidence: 99%
“…Providing reinforcers during momentary supervision checks will likely result in a delay to reinforcement, which could weaken the contingency or reduce the value of the reinforcers (Lannie & Martens, ; Reed & Martens, ). Lannie and Martens arranged for four typically developing fourth grade students to complete math work sheets in a concurrent schedules preparation.…”
Section: Introductionmentioning
confidence: 99%